Factors associated with the health and cognition of 6‐year‐old to 8‐year‐old children in KwaZulu‐Natal, South Africa. Issue 5 (3rd April 2017) - Ajayi, Oluwakemi R.; Matthews, Glenda; Taylor, Myra; Kvalsvig, Jane; Davidson, Leslie L.; Kauchali, Shuaib; Mellins, Claude A.
Abstract: Objective: To investigate 6‐year‐old to 8‐year‐old children's health, nutritional status and cognitive development in a predominantly rural area of KwaZulu‐Natal, South Africa. Methods: Cohort study of 1383 children investigating the association of demographic variables (area of residence, sex, pre‐school education, HIV status, height for age and haemoglobin level) and family variables (socioeconomic status, maternal and paternal level of education), with children's cognitive performance. The latter was measured using the Grover‐Counter Scale of Cognitive Development and subtests of the Kaufman Assessment Battery for Children, second edition (KABC‐II). General linear models were used to determine the effect of these predictors. Results: Area of residence and height‐for‐age were the statistically significant factors affecting cognitive test scores, regardless of attending pre‐school. Paternal level of education was also significantly associated with the cognitive test scores of the children for all three cognitive test results, whereas HIV status, sex and their socioeconomic status were not. Conclusion: Children with low cognitive scores tended to be stunted (low height‐for‐age scores), lacked pre‐school education and were younger. Area of residence and their parents' educational level also influenced their cognition.